Genetic Profile of an Oka Varicella Vaccine Virus Variant Isolated from an Infant with Zoster - Sauerbrei, Andreas (American Society for Microbiology, 2004)
Varicella virus vaccine strain Oka (V-Oka) has in rare cases caused zoster in vaccinated people. Despite broad usage of V-Oka, little is known about varicella-zoster virus genomic sequence variation of strains in vaccine and isolates from patients with vaccine adverse events. Direct sequencing of 20 regions of V-Oka-GSK was compared to the sequences of the original V-Oka-Biken, GlaxoSmithKline Oka vaccine (V-Oka-GSK), and Oka-parental (P-Oka) strains. We analyzed single nucleotide polymorphisms (SNP) differentiating the Oka parental and Oka vaccine strains identified in open reading frames (ORFs) 6, 9A, 10, 21, 31, 39, 50, 51, 52, 54, 55, and 59 and eight base substitutions within ORF 62. Sixteen of these SNP impose an amino acid change in the corresponding gene product. The genotypic analysis revealed that (i) both V-Oka-GSK and V-Oka-Biken comprise mixtures of strains represented in variable proportion from lot to lot; (ii) V-Oka-GSK/zoster isolated from the zoster patient had six wild-type SNP in ORF 9A, 10, 21, 52, 55, and 62 (mutation 108838); (iii) none of the six revertant SNP would reliably discriminate Oka vaccine from the wild type; and (iv) the genomic variation found in V-Oka/zoster might be associated with changes in the biological behavior of the virus. Further studies will be needed to identify potential virulence factors in variant vaccine strains.